KAJIAN PENERAPAN TUGAS MINI RISET TERHADAP HASIL BELAJAR MAHASISWA MATERI KEANEKARAGAMAN HAYATI - Abdul Hakim Daulae; Lazuardi Lazuardi; Martina Asiati Napitupulu (Universitas Negeri Medan, 2018)
This study aims to find empirical data about the application of mini research tasks to student learning outcomes in the course of Systems Biology at FMIPA Unimed Medan. The method used in this research is quasi experiment with nonequivalent control group design. The results showed that students' ability in mastery of biodiversity material given task with mini research on value (post-test) was higher with mean value (95) than control class (70). In addition, the mastery of communication skills in writing, oral presentation skills, skills of analysis / critical thinking and integration skills is higher than the control class. Thus it can be said that the application of mini research tasks to students who follow the course of Systems Biology in FMIPA Unimed can improve learning outcomes in the mastery of biodiversity lesson materials. Likewise can improve the ability of students in the mastery of communication skills in writing, oral presentation skills, skills of analysis / critical thinking and integration skills. The results of this study will be used as a refinement of Basic Biology learning guide in FMIPA Unimed.Keywords: Mini research, Biodiversity, Student learning outcomes